2023
DOI: 10.1002/agj2.21314
|View full text |Cite
|
Sign up to set email alerts
|

Properties and chemical compositions of monovarietal virgin olive oil at different ripening stages: A study on olive cultivation in Northwest China

Abstract: The olive management in China is rarely reported. This study evaluates the influence of drupes ripening on virgin olive oil (VOO) quality of four main varieties (Olea europaea L., cultivars Ezhi‐8, Koroneiki, Leccion, and Frontoio) cultivated in Northwest China. Quality indices, fatty acid profiles, polyphenols, terpenic acids, tocopherols, and squalene contents are tested at four ripening stages from September to November. The contents of linolenic acid, saturated fatty acids, triterpenic acids, and squalene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 89 publications
(159 reference statements)
0
4
0
1
Order By: Relevance
“…We found that α-tocopherol decreased in the EVOO produced from olives of medium RI. Previous studies have reported that vitamin E concentration in EVOO differs with the RI, diminishing or increasing according to the cultivar (Zhang et al, 2023). Finally, a decrease in apigenin was also associated with the medium RI.…”
Section: Ripeningmentioning
confidence: 69%
“…We found that α-tocopherol decreased in the EVOO produced from olives of medium RI. Previous studies have reported that vitamin E concentration in EVOO differs with the RI, diminishing or increasing according to the cultivar (Zhang et al, 2023). Finally, a decrease in apigenin was also associated with the medium RI.…”
Section: Ripeningmentioning
confidence: 69%
“…Chen et al, 2023;Chen & Shen, 2023;C. Guo, Yuan et al, 2023;Li et al, 2022;Liu et al, 2023;Mohammadpur et al, 2023;Qi et al, 2023;Shivashimpar et al, 2023;Yu et al, 2022;Zhang et al, 2023).…”
Section: Discussionunclassified
“…Useful approaches should involve multiple practices, adapt to different sites, and respond to farmers and community requirements. The research articles published in the special section “Agricultural and biological sciences: Plant, soil, animal and environment” address actual topics for agriculture and biology, covering smart technologies, bioinformatics, sensors in agriculture, rhizosphere microbiomes, mycorrhizal fungus and nano potassium fertilizer, IAHP, FCE, soil management, water efficiency, plastic‐film mulching technology, crop breeding, direct seeding, fruit growing management, and multi‐sensor data (C. Chen et al., 2022; X. Chen et al., 2023; Chen & Shen, 2023; C. Guo, Yuan et al., 2023; Li et al., 2022; Liu et al., 2023; Mohammadpur et al., 2023; Qi et al., 2023; Shivashimpar et al., 2023; Yu et al., 2022; Zhang et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations